If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(a + -4) = 16 Reorder the terms: 4(-4 + a) = 16 (-4 * 4 + a * 4) = 16 (-16 + 4a) = 16 Solving -16 + 4a = 16 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 4a = 16 + 16 Combine like terms: -16 + 16 = 0 0 + 4a = 16 + 16 4a = 16 + 16 Combine like terms: 16 + 16 = 32 4a = 32 Divide each side by '4'. a = 8 Simplifying a = 8
| 5(f-3)=-35 | | 10(s-3)=-58 | | 9x-3x=2x+20 | | 4x-(2x-8)=5(1+2x) | | 0.5x-7=3.9x-24 | | 7z-7=8 | | -3.6-6x=3.0 | | 18x-9-3x=36+3x | | x-1.2=2.2 | | 5t=5n+5v | | 7(3p+8)=2(p+9) | | 5x-10=6x+5 | | 1+2-51=8 | | 4y=300 | | (2x-7)+8x=(8x+28)+48 | | 16x+(30-x)26=18*30 | | 6x+9=-31-2x | | 8-3k=-4k+3 | | 27/-3=0 | | 66=2+8j | | 6x-18=3-12+4x | | 2+8x=-26+x | | 13x-4x-0= | | 6x+6=7x-14 | | 9m-27=45 | | 5h-7=3h-15 | | 6(b-2)+24=42 | | 4r+4=9r+14 | | 7p-5=4p+4 | | -2+26=6 | | 12+4=x | | -18+24x+2x=8x+88 |